2018
DOI: 10.2147/ijn.s172493
|View full text |Cite
|
Sign up to set email alerts
|

Different aggregation and shape characteristics of carbon materials affect biological responses in RAW264 cells

Abstract: IntroductionCarbon nanotubes (CNTs) have various shapes, including needle-like shapes and curled shapes, and the cytotoxicity and carcinogenicity of CNTs differ depending on their shapes and surface modifications. However, the biological responses induced by CNTs and related mechanisms according to the dispersion state of CNTs have not been extensively studied.Materials and methodsWe prepared multiwalled CNTs (MWCNTs) showing different dispersions and evaluated these MWCNTs in RAW264 cells to determine cytotox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 50 publications
1
9
0
Order By: Relevance
“…This highuptake and low-toxicity of CNT agglomerates can facilitate drug/gene delivery through regulating agglomeration of CNTs in some delivery systems. Kuroda et al 65…”
Section: Degree Of Agglomeration and Aggregationmentioning
confidence: 99%
“…This highuptake and low-toxicity of CNT agglomerates can facilitate drug/gene delivery through regulating agglomeration of CNTs in some delivery systems. Kuroda et al 65…”
Section: Degree Of Agglomeration and Aggregationmentioning
confidence: 99%
“…Considered collectively, the various and often conflicting studies describing the effects of oxidation on CNT toxicity can be understood by the differential interaction of CNTs with cells based on aggregation state and the specific mechanism of toxicity, both of which vary depending on the organism of interest . Surface oxidation can promote toxic effects which manifest through certain pathways (e.g., DNA damage) but reduce toxic effects which emerge via others (e.g., membrane disruption) by virtue of the changes in dispersibility and membrane interactions produced by the addition of surface oxygen groups.…”
Section: Environmental Risk and Toxicitymentioning
confidence: 99%
“…Of the CNMs used in this study, the uptake weight of MWCNT was the highest at both time points. We previously compared the uptake of well-dispersed MWCNTs and CNHs by macrophage-like Raw264 cells, and reported that CNH was taken up but MWCNT was hardly taken up [30]. These results indicate that the cellular uptake mechanism of fibrous and spherical CNMs varies depending on the cell type.…”
Section: Discussionmentioning
confidence: 89%
“…We have already reported that the dispersion state of CNMs affects some cell lines differently [29,30]; accordingly, we first examined the dispersion state of the CNMs used in the aqueous solution. The sonicated CNMs were measured with a Zetasizer Nano ZS first (Table 1), and their shapes were observed with a TEM (Figure 1).…”
Section: Characterization Of Dispersed Cnmsmentioning
confidence: 99%